Pengaplikasian nilai-nilai pancasila pada media sosial dalam penyebaran informasi - Faiz, Hafizah; Putri, Adisty Nadia; Ramadhan, Olivia Itka Nishfi (Maliki Interdisciplinary Journal, 2024)
The aim of this research is so that the millennial generation can use social media wisely and apply the values ​​of Pancasila in it. Many negative issues have been found, both from groups and individuals. Tendency to attack each other in the form of provocation, hate speech, slander, fraud, and so on. The spread of news nowadays, especially on social media, is very fast and massive. There is even a special term created to describe news that spreads very quickly and becomes famous, namely "viral". Social media platforms are a means of implementing Pancasila values. By adhering to the values ​​of Pancasila, the state’s position will be guaranteed and the nation’s integrity will remain strong. Internet network communication media can be the cause of socio-cultural changes in a negative direction.